(3GdETGQI Edi SjQI GdeUWaj hBKGQ ef HYOg ef GdNdaGs - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s ((3SYO Hf MSf Hf MSf GdeDOH s)
(3ChdgG (B:s
(3eZdWGi Hf bdjM GdbgGQ hGdUdGI hGdGWgGQ Edi JdNjU abOeJ GdESJNGQI ef cJGHi GdeSei HGdRgQ GdHGSe hdeG HdZ Ydjg GdUdGI hGdSdGe SJ YTQI SfI , hdO CHh WdMI GdCfUGQi s
(3BNQgG (B:s
(3hGSJhdi ghdGch Ydi GdHdGO , hCXgQ ai GdCQV GdaSGO , hNQH eOjfI GdSdGf , Hd eYbd GdESdGe adh cGf TGgOkG GdCShO Hf jYaQ dHci Ydjge dG Ydi EjGO hCQi GdfYje hcd eG jdgi Hg jhekG jUjQ Edi Hdi hfaGO hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde eVHhWs
(3HBNQgG bQGAI hSeGY ai eLGdS BNQgG ai LeGOi GdKGfjI ef SfI (B931(3g` HGdLGeY GdcHjQ GdCehis
(3ai GdeYgO fSN CNQi HQbe (B580 (3, (B889 (3, (B1367 " (3ecQQI ef GdChdi (B" (3JGQjN s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJGQjNs